AB0534 Does the Presence of ANCA in Patients with Lupus Nephritis (LN) Help to Distinguish A Subset?. (10th June 2014) - Neves, M.; Irlapati, R.V.P.; Isenberg, D.A.
Abstract : Background: Antineutrophil cytoplasm antibodies (ANCA) are known to occur in some patients with systemic lupus erythematosus (SLE), with a prevalence of 15 to 20% [1]. The perinuclear pattern (pANCA) predominates in this setting. Among SLE patients, ANCA positivity is more frequent in those with LN. ANCA positivity in LN patients was also associated with increased disease activity assessed by the SLE disease activity index (SLEDAI) [2]. Objectives: The aim of our study was to characterize a population of patients with LN that showed ANCA positivity and determine if they had any other distinguishing features. Methods: Patients with LN and an ANCA test result, both by immunofluorescence and enzyme-linked immunosorbent assay (ELISA), were retrospectively assessed. The parameters analyzed were age of onset of SLE and nephritis, gender, ethnicity, clinical manifestations, anti-dsDNA antibodies, antibodies to extractable nuclear antigens (ENA), and kidney histological classification (WHO). Results: Eight out of 67 patients with LN who had been tested (approximately 12%) had positive ANCA (pANCA 6 and cANCA 2). All were female. The mean age at SLE diagnosis was 27±17.7 years and the mean age at renal disease onset was 31.2±16.5 years. The clinical manifestations were as follows: arthralgia (n=7), skin rash (n=6), Raynaud syndrome (n=5), serositis (n=2), neurolupus (n=2), myositis (n=1). The incidence of Raynaud's in the ANCA positive LN cases was significantly higher than in the patients without ANCA (p=0.0211). Six patients had positive anti-dsDNA antibodies and 5 patients had positive antibodies to ENA. The kidney biopsies showed WHO class II in 2, class III in 1, class IV in 3 and class V in 2 patients. Overall, these figures were not distinguishable from the 195 patients in total with renal SLE that we have followed in the long term. Conclusions: We could not distinguish a clinical phenotype for our LN patients who were ANCA positive, although interestingly we noted a high prevalence of Raynaud's syndrome. Whether or not ANCA positivity can predict digital vasculitis in LN patients will need further studies. References: Sen D, Isenberg DA. Antineutrophil cytoplasmic autoantibodies in systemic lupus erythematosus. Lupus. 2003; 12: 651-658. Pradhan VD, Badakere SS, Bichile LS, Almeida AF. Anti-neutrophil cytoplasmic antibodies (ANCA) in systemic lupus erythematosus: prevalence, clinical associations and correlation with other autoantibodies. J Assoc Physicians India. 2004; 52: 533-537. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1606